Diagnostic accuracy and impact of fluorodeoxyglucose positron emission tomography/computed tomography in preoperative staging of cutaneous malignant melanoma: Results of a prospective study in Indian population - Piyush Chandra; Nilendu Purandare; Sneha Shah; Archi Agrawal; Ajay Puri; Ashish Gulia; Venkatesh Rangarajan (World Journal of Nuclear Medicine)
The aim of the study was to evaluate the diagnostic accuracy of positron emission tomography/computed tomography (PET/CT) in staging patients with primary cutaneous malignant melanoma (CMM). We further compared the performance of PET/CT with conventional imaging (CI) (CT and ultrasonography [USG]) and assessed the impact of PET/CT on disease management. This was a single institution, prospective, double-blinded study, recruiting a total of 70 treatment naïve patients. The sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) of PET/CT for N staging were 86%, 96%, 80%, and 97%, respectively. The sensitivity, specificity, NPV, and PPV of PET/CT for M staging were 87%, 100%, 93%, and 100%, respectively. The diagnostic accuracy of the PET/CT was superior to CI for N staging (90% vs. 84% for CT and 80% for USG) and M staging (95% vs. 90% for CT). No statistically significant difference was noted between PET/CT and CI for N staging (PET/CT vs. CT, P = 0.125; PET/CT vs. USG, P- 0.063) or M staging (PET/CT vs. CT, P = 0.125). PET/CT upstaged 23% of patients with clinically localized disease and 58% of patients with clinically palpable regional nodes. To conclude, fluorodeoxyglucose PET/CT is a highly sensitive and specific imaging modality for preoperative staging of primary CMMs. PET/CT impacts disease management in significant number of patients and should be especially recommended in all patients with clinically palpable regional nodes.